Mr. and Miss Anonymous - Michaels, Fern (Kensington Books, 2009)
Two teenage boys are missing and their disappearance may be linked to a shady fertility clinic Peter Kelly and Lily Madison visited in college as penniless students. When Pete and Lily learn that one of the missing boys looks exactly like Pete, they set out to discover what really went on at the clinic all those years ago.